2022
DOI: 10.1111/jog.15183
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of placental abruption with diffusion‐weighted imaging

Abstract: Aim: To investigate whether placental abruption without fetal distress could be assessed by apparent diffusion coefficient (ADC) values in magnetic resonance imaging (MRI). Methods: We conducted a retrospective case-control study at a single center. ADC values at the lesions of placental abruption in the abruption group (n = 8) were compared to those in the control group (n = 32). In the abruption group, ADC values at the sites of abruption were also compared to those at the nonabruption sites within the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although ultrasonography offers relatively high overall accuracy of nearly 90% for diagnosing placental abruption, its sensitivity may be only 57.0% [18].Further research should explore how to improve the diagnostic performance of ultrasonography for detecting or predicting placental abruption. It may also be possible to diagnose or predict the complication using magnetic resonance imaging [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although ultrasonography offers relatively high overall accuracy of nearly 90% for diagnosing placental abruption, its sensitivity may be only 57.0% [18].Further research should explore how to improve the diagnostic performance of ultrasonography for detecting or predicting placental abruption. It may also be possible to diagnose or predict the complication using magnetic resonance imaging [19].…”
Section: Discussionmentioning
confidence: 99%
“…US is still the first modality of choice for placental assessment, because of its safety and availability. However the overall diagnostic performance of US in the detection of PA is poor, with reported sensitivity of less than 25% and a negative predictive value from 14 to 53% [ 55 , 56 , 57 ]. The US appearance of PA correlates with the size and location of the bleeding, as well as the time elapsed between abruption and the examination.…”
Section: Obstetric Causesmentioning
confidence: 99%
“…The authors demonstrated that ADC values on the lesions above the PA site were significantly reduced compared to those in the control group. Moreover, in the abruption group, ADC values at the abruption site were also significantly lower than in the non-abruption site within the same placenta [ 57 ].…”
Section: Obstetric Causesmentioning
confidence: 99%